Time slot-based RED algorithm on self-similar flows:SFRED - WANG Hui; JI Zhen-zhou; SUN Yan-dong; WANG Yuan-zheng (Tongxin xuebao)
Based on fractional Brownian motion（FBM）,one calculation of the packet drop probability in the RED algorithm was derived under self-similar flows.Based on the self-similarity and the long-range dependence characteristics of Internet network traffics,a time slot-based RED algorithm on self-similar flows（SFRED） was proposed to the router queue management.The packet drop probability is calculated in every time-slot so that the burden is greatly reduced.It is simulated by NS2 and the experimental results show that the algorithm SFRED outperforms RED.SFRED can control the queue length under adaptive flows with a good throughput.